Tasawuf Wahdat Al-Wujud (Wujudiyah) Syekh Syamsuddin As-Sumatrani: Tarekat, Ajaran dan Amalan di Sumatera Barat Pada Abad Ke-16 dan 17 Masehi - Fikri Ramadhan; Putri Yuli` Fatmawati; Rosi Elsa Handayani; Yeny Dwi Lestari (Medan Resource Center, 2022)
This article aims to review the teachings of Wujudiyah brought by Sheikh Syamsuddin As-Sumatrani using the concept of the dignity of seven until his teachings could reach West Sumatra in the 16th and 17th centuries. Although there are pros and cons among scholars regarding this manifestation teaching and many works of the manifestation teaching were destroyed, this manifestation teaching is still spread through the relationship between teacher and student. This research is a literature research using historical research methods. Some manuscripts are used as primary sources and some relevant books and scientific articles are used as secondary sources. This study shows that the teachings of wujudiyah brought by Sheikh Syamsuddin As-Sumatrani successfully spread to West Sumatra through the support of Sheikh Abdurrauf As-Singkili who developed these teachings to his student Sheikh Burhanuddin Ulakan in West Sumatra.